Prevalence ratio of free fatty acid in obese group with non-alcoholic fatty liver disease - Rosmeri Handayani; Siti Muchayat Purnamaningsih; Usi Sukorini (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
Non-alcoholic fatty liver disease (NAFLD) is liver disorders characterized by macrovesicular fatty liver, fibrosis, cirrhosis that not associated with alcohol consumption. The prevalence of NAFLD has risen with a pandemic of obesity. The increase of free fatty acid (FFA) oxidation will induce endoplasmic reticulum stress that cause mitochondrial dysfunction and lead to increase reactive oxygen species (ROS) production causing apoptosis of liver cells. The aim of  study was to determine the prevalence of FFA in the obese group. This was an observational analytical study with cross-sectional design to determine the prevalence ratio of FFA in the obese group with NAFLD compared to the group without NAFLD. Obese women who fulfill the inclusion and exclusion criteria were involved in this study. Five mL venous blood sample was collected for the measurement of lipid profile, liver enzyme and FFA. Fatty liver was evaluated using abdominal USG. The Chi-square test was used to analyze different proportions of FFA between the both groups. Sixty four subjects were participated in this study and classified into obese with NAFLD (39 subjects) and obese without NAFLD (25 subjects). The prevalence ratio of FFA with cutoff value ≥2.66 nmol/mL in the obese group with NAFLD was 4.3 times higher than those without NAFLD (95% IC: 3.5 – 42.3; p<0.001).